2017
DOI: 10.1016/j.paid.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

High intrasexual competition is related to inflated height reports in male junior soccer players

Abstract: Intrasexual competition refers to the rivalry between same-sex individuals over access to potential mates. Because in many animal species larger males are more likely to defeat smaller opponents over access to potential mates and additional resources, it has been suggested that intrasexual competition was a major driver in the emergence of male-biased sexual size dimorphism. In the same vein, human male height has been related to aggressive behavior, status and dominance. Given the value of body size in agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In line with the foregoing, various studies have demonstrated a high intensity of physical intrasexual competition among adolescent men, as apparent in the display of risky behavior (e.g., Ellis et al, 2012 ) and in same-sex peer aggression (e.g., Gallup et al, 2011 ). Recently, Mailhos, Buunk, and del Arca (2017) found in adolescents a positive relationship between intrasexual competitiveness and overreporting one’s height. The authors noted that overestimation of one’s height could be interpreted as an indicator of status and physical dominance.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the foregoing, various studies have demonstrated a high intensity of physical intrasexual competition among adolescent men, as apparent in the display of risky behavior (e.g., Ellis et al, 2012 ) and in same-sex peer aggression (e.g., Gallup et al, 2011 ). Recently, Mailhos, Buunk, and del Arca (2017) found in adolescents a positive relationship between intrasexual competitiveness and overreporting one’s height. The authors noted that overestimation of one’s height could be interpreted as an indicator of status and physical dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Given this lack of consistent evidence, there is a clear need for more research to establish whether the subjective sense of one’s mate value and attractiveness is related to one’s height. In addition, most research in this area has employed self-reports of height, which may be subject to considerable bias (Mailhos, Buunk, & del Arca, 2017). Therefore, the present study examined in a sample of young couples from Chile whether objectively assessed height was associated with self-perceived mate value and self-perceived attractiveness, and if it was different for men and women.…”
mentioning
confidence: 99%
“…In contrast to earlier biological perspectives on human mating that suggested an inconsequential role of body size in marriage selection (Galton, 1886; see Stulp, Simons, Grasman, & Pollet, ), the current state of the art suggests the opposite—an important role of human height in self‐presentation (Mailhos, Buunk, & del Arca, ), self‐assessed mate value (Buunk, Fernandez, & Muñoz‐Reyes, ; Griffiths, Murray, Medeiros, & Blashill, ), attractiveness ratings and partner preferences (Shepperd & Strathman, ; Sorokowski et al, ; Stulp et al, 2013b; Yancey & Emerson, ; Valentova, Bártová, Štěrbová, & Varella, ), and mate choice (Frederick & Jenkins, ; Sohn, ; Stulp, Pollet, Verhulst, & Buunk, ; Tao, ; Tao & Yin, ). These studies indicate that in general, at least in western societies, relatively tall men and women within an average range are typically judged as most attractive by individuals of the opposite‐sex (see also Stulp & Barrett, for review).…”
Section: Introductionmentioning
confidence: 65%